2009
DOI: 10.1007/s00168-009-0325-4
|View full text |Cite
|
Sign up to set email alerts
|

Intra-regional residential movement of the elderly: testing a suburban-to-urban migration hypothesis

Abstract: The majority of the elderly and soon-to-be retired baby boomers live in suburbs in the US. This paper empirically tested an intra-regional residential movement of elderly households, which is postulated based on life course theory. Using data from the Puget Sound Transportation Panel survey in Washington State in the US, this study found that elderly households are less likely to change their residential environments than younger households upon intra-regional residential movement. This study also found that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Earlier research (see Kim, 2011) does suggest that single adult and single parent households tend to locate themselves in denser neighborhoods, so that they are able to partake easily in social and related activity opportunities. The effects of the family structure variables on the other dependent variables (see the columns titled "Counts" and "Linear Regression") are rather intuitive (the parameters in the columns for the count variables are coefficients corresponding to the l μ vector).…”
Section: Exogenous Variable Effectsmentioning
confidence: 99%
“…Earlier research (see Kim, 2011) does suggest that single adult and single parent households tend to locate themselves in denser neighborhoods, so that they are able to partake easily in social and related activity opportunities. The effects of the family structure variables on the other dependent variables (see the columns titled "Counts" and "Linear Regression") are rather intuitive (the parameters in the columns for the count variables are coefficients corresponding to the l μ vector).…”
Section: Exogenous Variable Effectsmentioning
confidence: 99%
“…This rise in the number of older adults will persist until approximately the year 2030, after which the number of older adults will drop due to the decreasing birth rates from the 1970s and onwards (van Iersel et al, 2010). the year 2030, after which the number of older adults will drop due to the decreasing birth rates from the 1970s and onwards (van iersel et al�, 2010)� The effect of these factors has been that the old-age dependency ratio, defined as the number of persons aged 65 and older as a percentage of the 20 to 64 year olds, gradually increased from 18�8% in 1970 to its current level of 25�2%� The old-age dependency ratio is expected to peak at 48�7% in 2040 (CBS, 2010)� as the number and proportion of older people in our society changes, these processes will have numerous implications (Kim, 2011)� The increase of older adults, together with a decrease in the number of younger people, will place an enormous burden on existing income systems, health care systems, social services and retirement programs� older adults are likely to demand a wide array of new services to meet their unique and diverse needs (Choi and dinse, 1998)� The changing age composition will also affect the geographical mobility of populations (Plane and rogerson, 1991), reshaping the physical environment as we know it (Kim, 2011)� This research aims to provide more insight into the residential moving behaviour of older adults in the netherlands� This paper will first present theoretical frameworks which have been applied to the residential mobility of older adults� next, the discrepancy in defining the older adults in the literature will be discussed� The paper will continue with several descriptive analyses demonstrating the difference between older adults that moved and older adults that did not move between the years 2007 and 2009� lastly, some suggestions for future research are given�…”
Section: Introductionmentioning
confidence: 99%
“…In regards to retirement migration, the literature has traditionally suggested that retirees tend to move to lower‐density areas or out of large metropolitan areas entirely (Litwak and Longino ; Plane, Henrie, and Perry ). In an analysis of migration outcomes in the Seattle area, Kim () does observe a slight tendency of older residents to migrate to more‐urban destinations; however, the magnitude of these moves was not large, as the elderly had a lower propensity to migrate. Indeed, life‐course status figures prominently in Kim's study; while single migrants were likely to choose more urban destinations, migrants with children tended to opt for low‐density suburbs.…”
Section: “Back‐to‐the‐city” or A Suburban Status Quo For American Migmentioning
confidence: 99%